Environmental Sustainability in the Fourth Industrial Revolution: The Nexus between Green Product and Green Process Innovation - Saudi, Mohd Haizam Mohd; Sinaga, Obsatar; Roespinoedji, Djoko; Razimi, Mohd Shahril Ahmad (International Journal of Energy Economics and Policy, 2019)
The actual and virtual realms in the present economies are expending to respond well to technological evolutions. In fact, the emergence of fourth industrial revolution has stimulated the organization to adopt innovations in the production and process with extensive integration of eco-friendly practices to ensure sustainability. The automation of work and emerging digitalization is known as the fourth industrial revolution. This industrial revolution has several effects on person's career involvements. Still, the past literature in careers research and vocational psychology has been surprisingly quiet on this pattern up until now. In this regard, the present study examines the impact of industrial revolution factors on environmental and economic performance in manufacturing SMEs in Malaysia. The results of structural equation modeling confirm that green product innovation and green process innovation have positively and significant impact on project innovation. Moreover, the results further confirm that project innovation has positive and significantly impact on economic performance and environmental performance. Finally, economic and environmental performance have a positive and significant impact on competitive advantage. Therefore, it is recommended that fourth industrial revolution factor is a source to enhance the economic and environmental performance of the firm which ultimately leads the competitive advantage. Keywords: Projection innovation, process innovation, environmental performance, competitive advantage, SME's, Malaysia JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8281